ASSESSING VALUATION MODEL FORECASTING ACCURACY IN HEALTHCARE: A SIMULATED COMPARISON OF CAPM AND DDM - Wil Martens (ZILLZELL MEDIA PRIMA, 2025)
This study addresses the challenges of valuing firms in the volatile healthcare sector by rigorously comparing the fore- casting accuracy of the Capital Asset Pricing Model (CAPM) and the Dividend Discount Model (DDM). Employing a controlled synthetic dataset of 100 healthcare firms spanning 2019–2021, we aim to isolate model performance, free from real-world confounding factors. Forecast accuracy is measured using Mean Absolute Error (MAE) and Percent- age Absolute Error (PAE). Results indicate CAPM significantly outperforms DDM (e.g., CAPM’s average PAE of 3.47% vs. DDM’s 8.48%), particularly due to healthcare’s variable dividend policies. This research provides empirical evidence from a controlled setting on model suitability, guiding financial practitioners toward more reliable valuation techniques and contributing to the literature on model selection in sector-specific financial contexts.